KOTA BAJA, PEMEGANG UMK KE-6 TERTINGGI DI INDONESA SEBAGAI TUJUAN MIGRASI - Lidya Fadila; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
Cilegon City, known as Kota Baja (Steel City), is a major industrial center in Indonesia with diverse sectors such as petrochemicals, metals, steel, and chemicals. This industrial growth has made Cilegon an attractive migration destination for individuals from outside Banten Province. This research uses quantitative methods to analyze statistical data and secondary data from previous studies. The results indicate that Cilegon City's high regional competitiveness is a key factor in attracting migrants. Migration in Cilegon is not only influenced by economic factors such as job opportunities and high minimum wages but also impacts demographic dynamics, labor availability, and challenges related to urban infrastructure. The city experiences various migration patterns, including internal, seasonal, family, and return migration. Effective migration management is crucial to ensure sustainable city development and community welfare. Factors such as economic development, unemployment rates, and economic inequality balance are also significant in shaping Cilegon's attractiveness as a migration center.